Review and gap analysis of Water Sensitive Urban Design (WSUD) in Windhoek, Namibia - Nambinga, Linekela Elias (Department of Civil Engineering, 2020)
With an ever-increasing population and global warming, fresh water resources are nearing depletion resulting in a global water crisis. As a consequence, cases of drought have been reported worldwide especially in sub-Saharan Africa. In addition to climate change, urbanisation adds strain to infrastructure as well as water supply and the management of water resources. As a result, most developing countries are faced with a water management challenge. There is thus a need for a paradigm shift towards an Integrated Water Management (IWM) approach. Worldwide, countries have responded to the Integrated Urban Water Management (IUWM) concept through the implementation of various management strategies; with Water Sensitive Urban Design (WSUD) emerging from Australia. Some closely allied management strategies in response to IUWM emerged in the USA as Low-Impact Development (LID), in the UK as Sustainable Drainage Systems (SuDS), and in New Zealand as Low-Impact Urban Design and Development (LIUDD). Namibia is situated along the south-west coast of Africa and is considered the driest country in sub-Saharan Africa. It is characterised by a semi-arid environment, with more than 80% covered by desert or semi-desert. The country is regularly afflicted by drought and has fluctuating and unreliable rainfall patterns, often accompanied by high evaporation rates. The City of Windhoek, as the capital city, the biggest municipality and also the largest densely populated town in Namibia, is faced with an ever-increasing shortage of water for its inhabitants. For close to 50 years, the water scarcity situation has led to direct waste water reclamation for potable re-use in Windhoek. Other measures implemented by the City of Windhoek (CoW) towards IUWM include Water Demand Management (WDM), Managed Aquifer Recharge (MAR) and Water Conservation (WC). In order for Windhoek to transform into a Water Sensitive City, the implementation of WSUD is imperative. Although the CoW has implemented measures towards IUWM, more options still need to be explored in order to contribute to IUWM processes and to ultimately become a Water Sensitive City. This research was aimed at conducting a comprehensive review of existing WSUD practices within the CoW and identifying gaps pertaining to WSUD implementation. The research confirmed, via a review of relevant literature, that the implementation of WSUD mainly flourishes when documented policies and regulations drive implementation. To review WSUD implementation in the CoW, this study followed a qualitative research approach by gathering data via online questionnaires using the SurveyMonkey platform. To validate the survey outcomes, structured interviews were conducted with selected survey participants to gain more insight into the outcomes. For the data collection, the study targeted a sample of managers and specialists from the three departments within the CoW that deal with urban infrastructure design and planning. A 72% response rate was achieved. The study revealed that there was a general understanding and knowledge of WSUD concepts among all the CoW stakeholders involved in water management, planning and design. This was mostly due to their academic knowledge and sometimes via exposure to existing WSUD practices within the city. Water Demand Management, Water Recycling, and Voluntary Green Roofs and Rainwater Harvesting were identified as existing WSUD options currently practised within the CoW. The study identified lack of capacity, lack of knowledge, lack of management support, a fragmented approach, the absence of policies and legislation, and no perceived financial benefits as barriers to WSUD implementation within the CoW. Based on the above findings, the study recommended that the City of Windhoek address existing barriers to WSUD implementation, increase awareness of WSUD within the city, secure government funding and apply for carbon credits to upscale the implementation of WSUD.